Beauty Representation (Semiotic Analysis of Roland Barthes in Rachel Goddard Youtube Account) - Afrilia Wening Anindya; Dr. Lintang Ratri Rahmiaji, M.Si (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2017)
This research was started from beautiful meaning that remains a problem for women and still debated to this day. Rapid technological development, until the advent of vlog makes the concept of beauty changes. One of vlogger that discusses about beauty on her YouTube account is Rachel Goddard. She presents vlog about makeup tutorials, tips on caring for the body and face, also reviews on beauty products through her youtube account. The aim of this research is to know the beauty representation based on Semiotic analysis and also to dismantle the myth of what was built by Rachel Goddard. In analyzing vlog about beauty tutorials titled